2009
DOI: 10.1080/00365520902718713
|View full text |Cite
|
Sign up to set email alerts
|

Function and dysfunction of the colon and anorectum in adults: Working team report of the Swedish Motility Group (SMoG)

Abstract: Symptoms of fecal incontinence and constipation are common in the general population. These can, however, be unreliably reported and are poorly discriminatory for underlying pathophysiology. Furthermore, both symptoms may coexist. In the elderly, fecal impaction always must be excluded. For patients with constipation, colon transit studies, anorectal manometry and defecography may help to identify patients with slow-transit constipation and/or pelvic floor dysfunction. The best documented medical treatments fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 157 publications
0
8
0
Order By: Relevance
“…Intuitively, there is no problem understanding that rectal problems might arise after major urological pelvic surgery such as cystectomy with urinary tract reconstruction, as they do after other pelvic surgical procedures [23–25]. The colorectal physiology is complex and includes many different stages of the stool evacuation process [26]. More systematic research is needed for this to be discussed and handled during urological postoperative controls.…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, there is no problem understanding that rectal problems might arise after major urological pelvic surgery such as cystectomy with urinary tract reconstruction, as they do after other pelvic surgical procedures [23–25]. The colorectal physiology is complex and includes many different stages of the stool evacuation process [26]. More systematic research is needed for this to be discussed and handled during urological postoperative controls.…”
Section: Discussionmentioning
confidence: 99%
“…FI is a multifactorial disorder associated with decreased quality of life (QoL) [5][6][7][8][9][10][11]. However, Bordeianou et al recently found that the severity of FI was only moderately correlated with a disease-specific QoL measurement [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence increases with age [5], and after 50 years of age, prevalence rates up to 22% in women have been reported [2]. In elderly living in institutions, the prevalence has been found to range between 10% and 50% [4]. Whitehead et al reported that most participants with FI suffered from 1 to 3 leakages per month [3].…”
Section: Introductionmentioning
confidence: 99%
“…Fecal incontinence (FI) affects 2.2-15.3% of an adult general population [1][2][3][4]. The prevalence increases with age [5], and after 50 years of age, prevalence rates up to 22% in women have been reported [2].…”
Section: Introductionmentioning
confidence: 99%